2013
DOI: 10.1080/02699931.2013.854195
|View full text |Cite
|
Sign up to set email alerts
|

How does emotion influence different creative performances? The mediating role of cognitive flexibility

Abstract: Cognitive flexibility is proposed to be one of the factors underlying how positive emotions can improve creativity. However, previous works have seldom set up or empirically measured an independent index to demonstrate its mediating effect, nor have they investigated its mediating role on different types of creative performances, which involve distinct processes. In this study, 120 participants were randomly assigned to positive, neutral or negative affect conditions. Their levels of cognitive flexibility were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 28 publications
1
63
0
2
Order By: Relevance
“…Furthermore, our results suggest that during clinical reasoning the mPFC may work in tandem with the parahippocampal gyrus to enhance social perception, empathy and mentalizing, which may facilitate making appropriate judgments about fMRI correlates of the DTI patient health (Vollm et al 2006). In fact, prior neuroimaging research suggests that the vmPFC may be strongly influenced by emotional saliency during reasoning (Goel & Dolan 2003), so our findings could be construed to depict the impact of affective processes during analytic reasoning rather than creativity; however, there is some evidence that cognitive flexibility mediates of emotional and creative thinking (Lin et al 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, our results suggest that during clinical reasoning the mPFC may work in tandem with the parahippocampal gyrus to enhance social perception, empathy and mentalizing, which may facilitate making appropriate judgments about fMRI correlates of the DTI patient health (Vollm et al 2006). In fact, prior neuroimaging research suggests that the vmPFC may be strongly influenced by emotional saliency during reasoning (Goel & Dolan 2003), so our findings could be construed to depict the impact of affective processes during analytic reasoning rather than creativity; however, there is some evidence that cognitive flexibility mediates of emotional and creative thinking (Lin et al 2014).…”
Section: Discussionmentioning
confidence: 75%
“…The effect of interpersonal conflict on project performance by Lessing the dysfunctional effect is the focus of research. In the past researches, a contingency approach was used to examine the interpersonal conflict (Huang, 2012;Lin et al, 2014). It is established by the likelihood view of the effects of interpersonal/social conflict that the way and amount of the effects will depend on the impact of related factors (Huang, 2012;Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the past researches, a contingency approach was used to examine the interpersonal conflict (Huang, 2012;Lin et al, 2014). It is established by the likelihood view of the effects of interpersonal/social conflict that the way and amount of the effects will depend on the impact of related factors (Huang, 2012;Lin et al, 2014). The moderating role of objective positioning on the relationship between clashes "Interpersonal/social conflict" and "Team performance" is explored by Huang (2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand some studies induced positive emotions and observed broadening effects, among others, on memory by increasing memory for the central and peripheral details (Yegiyan and Yonelinas, 2011), on visual attention shown by longer peripheral fixation time in an eye tracking experiment (Wadlinger and Isaacowitz, 2006), or on cognitive flexibility indicated by lower switch costs between tasks (Lin et al, 2014). Furthermore, building effects of positive emotions with regard to three different personal resources could be observed performing a path analysis of a questionnaire study conducted among army wives (Dolphin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%